Metastatic malignancy presenting initially as Acute Kidney Injury: Prospective follow up of six cases - Mahbub, Tania; Niger, Chowdhury Rifat; Akter, Salina; Khanam, Rawshan Arra (Bangladesh Critical Care Journal, 2020)
Acute kidney injury (AKI) is a significant complication in patients with cancer and is associated with high morbidity and mortality. Rates of AKI vary in cancer patients on the basis of several factors, including types of malignancy (either solid tumor or hematologic), stage of malignancy, associated complications such as critical illness, and type of supportive or interventional therapy given to the patient. AKI is a common finding within the patients diagnosed as malignancy. However, AKI as initial presentation of malignant disease is uncommon. Six cases of metastatic malignancy presenting initially as acute kidney injury are reviewed in this prospective study. We have reviewed one case of metastatic small cell carcinoma of lung, one case of metastatic carcinoma of rectum, one case of metastatic carcinoma, of lung with Horner’s syndrome, one case of metastatic pancreatic carcinoma and one case of metastatic squamous cell carcinoma of cervix. Out of them, two patients needed hemodialysis during hospital stay. Bangladesh Crit Care J March 2020; 8(1): 29-32